Sarcasm in William Shakespeare’s Drama Much Ado About Nothing - Syamsul Bahri; Putri Naira; Farid Rizaldi; Yolanda Marchella; Fitra Aulia Simatupang (International Journal of Multilingual Education and Applied Linguistics, 2026)
Sarcasm is a literary device and one of the most expressive forms of figurative language, often used to convey humor, criticism, or emotional tension in both daily conversation and literature. This study explores the use of sarcasm in William Shakespeare‟s Much Ado About Nothing by applying Elizabeth Camp‟s (2011) typology, which classifies sarcasm into four types: propositional, lexical, illocutionary, and like-prefixed sarcasm. Using a qualitative descriptive method, the researchers collected all sarcastic utterances from the play, classified them according to Camp‟s framework, and analyzed their pragmatic functions in the dramatic context. The findings reveal a total of 50 sarcastic utterances, with propositional sarcasm being the most frequent (42%), followed by illocutionary sarcasm (28%), lexical sarcasm (24%), and like-prefixed sarcasm (6%). These results indicate that sarcasm serves as both a comedic and dramatic device, shaping character interactions, driving conflicts, and reinforcing Elizabethan cultural norms. Beatrice and Benedick‟s witty verbal duels exemplify how sarcasm fosters humor and intimacy, while Claudio‟s sarcasm highlights themes of honor and social tension. Overall, the study demonstrates that sarcasm in Shakespeare‟s play is not merely humorous banter but a sophisticated rhetorical strategy that enhances characterization, thematic depth, and audience engagement.